Web-Based Material Inventory Information System For ALAR Welding Workshop - Probonegoro, Wishnu Aribowo; Sari, Lili Indah (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2025)
The ALAR welding workshop is a welding industry that welds various types of metal using various methods and techniques. Material inventory is crucial in this business. Currently, material inventory recording is still done manually, resulting in frequent data errors, information delays, and difficulties in tracking inventory, as it is still manually calculated. Given these issues, the author designed and built a web-based material inventory information system to help manage material stock effectively and accurately. This system replaces error-prone manual processes and improves operational efficiency at the ALAR welding workshop. The method used in this study is the waterfall method because it has a step-by-step design process, namely needs analysis, system design, implementation, testing, and system maintenance. The research results show that the developed information system can facilitate workshop staff in recording, monitoring, and reporting material inventory in real time. This system also improves data accuracy, time efficiency, and supports owners in making faster decisions in the material procurement process, because it is supported by actual and well-documented data. Therefore, this web-based inventory information system can be an effective solution for material management at the ALAR Welding Workshop.